Prevalence of lameness, claw lesions, and associated risk factors in dairy farms in Selangor, Malaysia - Babatunde, Sadiq Mohammed; Ramanoon, Siti Zubaidah; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah; Shaik Mohamed Mossadeq, Wan Mastura (Springer, 2017)
The objectives of this cross-sectional study were to estimate the prevalence of lameness, claw lesions, and associated risk factors in dairy farms in Selangor, Malaysia. The sample population was 251 lactating cows from 8 farms assessed for lameness and claw lesions by locomotion scoring and claw assessment respectively while specific animal-based measures were hypothesized as cow-level risk factors. The Wilcoxon rank test and logistic regression were applied to assess the prevalence of lameness, claw lesions, and association with potential risk factors, respectively. The prevalence of lameness was 19.1% ranging from 10.0 to 33.3% while 31.1% of cows had claw lesions and ranged from 16.3-40%. Claw lesions were recorded in 87.5% of the lame cows with highest being those affected with sole lesions (54.2%) and white line disease (61.2%). Overall, the occurrence of overgrown claws, sole lesions, white line disease, and digital dermatitis were 37, 18.2, 10.9, and 8.3%, respectively. More than one claw lesion per cow was present in 71.8% of the affected cows. Lameness was associated with early lactation (OR = 3.3; 95% CI 2-7), injured hocks (OR = 4.8; 95% CI 5-17), and dirty legs hygiene (OR = 2.6; 95% CI 1.3-6.2), whereas presence of claw lesions was associated with dirty legs hygiene (OR = 4.7; 95% CI 4-11) and overgrown claw (OR = 2.7; 95% CI 1.4-5.3). To reduce the prevalence of lameness, farmers need to improve the management of cows with overgrown claw, injured hocks, and cleanliness by establishing routine claw trimming and efficient stall design.